Intensifying Waste Management on Guam: Insights from Consumption Behaviour and Composting Initiatives - MH Golabi; Kirk Johnson; Takeshi Fujiwara; Eri Ito (Research Advances in Environment, Geography and Earth Science Vol. 7, 2024)
This study presented the efficacy of knowledge-based resource-recovery management to transform municipal waste into a valuable soil conditioner. Guam is a small, isolated tropical island in the western Pacific with a population of over 160,000 people. Although population growth and life style have been shown to have strong effects on the character and generation of waste, very little is known about consumption patterns and behavior of the people of Guam in this regard. Currently landfilling is the only discard method available to the island. Rapid increases in the volume and variety of solid and hazardous waste as a result of continuous economic growth, urbanization, and industrialization are a burgeoning problem for national and local governments, which must ensure effective and sustainable management of waste. Placement of huge volumes of organic waste material in landfills not only causes environmental problems for the island but in fact constitutes loss of valuable resources that could be composted and made available for land application as a soil amendment in forest lands, farm fields, and home gardens. Composting on the other hand reduces both the volume and the mass of the raw material while transforming it into a valuable soil conditioner. Here we present some of the results of survey questionnaires that was developed and conducted over the past two years that is anticipated to help waste operating managers and decision makers to determine societal consumption behavior and residential life style as the first step toward development of an effective waste-management strategy for the island of Guam. In this regards, we also presented an example of a large scale composting method developed in Isfahan, Iran, for recycling of organic wastes of municipal origin. Different zero-waste management strategies and techniques have been developed and adopted in different countries [1], but the strategy used in the city of Isfahan, Iran, which includes large-scale mechanical composting as a major component is of particular interest to Guam and the neighboring islands in the Micronesian region.